Screening of rectal swab specimens for vibrio parahaemolyticus in diarrheic patients at San Lazaro Hospital for kanagawa phenomenon reaction and urease activity - Chung, Edgar S. (1999)
The occurrence of two of the virulence markers of Vibrio Parahaemolyticus was determined in 10 culture-proven cases from 1,320 gastroenteritis patients admitted to San Lazaro Hospital from 19 October 1998 to 12 May 1999. Kanagawa phenomenon (KP), a reaction observed as a zone of beta hemolysis around the colonies of V. parahaemolyticus in Wagatsuma agar that is caused by a toxin known as Thermostable Direct Hemolysin (TDH), and urease activity, a biochemical reaction that has been shown to aid the survival of organisms in the host, were determined.In this study, V. parahaemolyticus was isolated in o.76of gastroenteritis cases. No KP negative isolates were obtained. all isolates exhibited the KP in Wagatsuma agar within 24 hours of incubation. KAP-RPLA "Seiken" method (Denka Seiken, Tokyo, Japan), an immunological diagnostic kit for detecting V. parahaemolyticus TDH by reversed passive latex agglutination, was also used to validate the findings. The results showed that KAP-RPLA "Seiken" method is comparable to, and easier to perform than using the Wagatsuma agar method. Moreover, all the isolates obtained in this investigation hydrolyzed urea. This is the first report made on the KP reactions of the local isolates and the occurrence of urease positive strains in the Philippines.In conclusion, the use of KP reactions as an epidemiological marker for virulence has been provided with a reasonable justification in this study. The results obtained from this study also showed that urea-hydrolyzing strains that produced or possessed TDH were the predominant biotype of gastroenteritis-causing V. parahaemolyticus isolated from San Lazaro Hospital. The body of knowledge that has been acquired from this study may served as a baseline information to further study the dynamics of bacterial virulence of V. parahaemolyticus and other potentially pathogenic bacterial species in the natural environment.
Thesis (MS Public Health, Medical Microbiology)--University of the Philippines Manila.
Keywords: Vibrio parahaemolyticus